The lncRNA male-specific abdominal plays a critical role in Drosophila accessory gland development and male fertility. - Maeda, R.K.; Sitnik, J.L.; Frei, Y.; Prince, E.; Gligorov, D.; Wolfner, M.F.; Karch, F. (PLoS Genetics, 2018)
Although thousands of long non-coding RNAs (lncRNA) have been identified in the genomes of higher eukaryotes, the precise function of most of them is still unclear. Here, we show that a >65 kb, male-specific, lncRNA, called male-specific abdominal (msa) is required for the development of the secondary cells of the Drosophila male accessory gland (AG). msa is transcribed from within the Drosophila bithorax complex and shares much of its sequence with another lncRNA, the iab-8 lncRNA, which is involved in the development of the central nervous system (CNS). Both lncRNAs perform much of their functions via a shared miRNA embedded within their sequences. Loss of msa, or of the miRNA it contains, causes defects in secondary cell morphology and reduces male fertility. Although both lncRNAs express the same miRNA, the phenotype in the secondary cells and the CNS seem to reflect misregulation of different targets in the two tissues.